Genome editing in banana: tools, techniques, and challenges - Tripathi, J.; Kariuki, S.M.; Waweru, D.N.; Tripathi, L. (Springer, 2025)
Bananas (Musa spp.) are one of the most important staple crops and fruit sources, providing livelihoods for millions of farmers in tropical and subtropical regions worldwide. It is cultivated in over 145 countries and small island nations, crucial to food security. However, banana production faces significant challenges due to various biotic and abiotic factors. The bananas’ narrow genetic diversity and long generation cycle make conventional breeding methods difficult and time-consuming. Genome editing offers a powerful approach to developing high-yield, disease-resistant banana varieties. Several genome editing technologies enable precise and targeted modifications within the plant genome. Among these, Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)-based tools stand out for their significant advantages, though they also present regulatory and technical challenges. In this chapter, we describe the importance of banana cultivation, examine the benefits and limitations of various CRISPR tools, explore advancements in banana genome editing, and cover the technical and regulatory aspects of implementing genome editing for banana improvement.